Proactive Caching and Forwarding Schemes for Seamless Handover in IEEE WAVE Networks. (10th December 2013) - Chung, Young-uk; Lee, Hyukjoon; Choi, Yong-Hoon; Lee, Chungwon
Abstract : The IEEE Wireless Access for Vehicular Environment (WAVE) standard consists of the IEEE 802.11p and the IEEE 1609 specifications supporting fast link establishment as well as broadband data communication in vehicular environment. Although the standard has been widely accepted by industry as well as highway authorities in many countries to be used for the radio communication infrastructure of the next-generation Intelligent Transport System (ITS), it remains open for further enhancements such as seamless handover support. This paper presents two proactive caching and forwarding schemes for seamless handover in IEEE WAVE networks: one for straight highway sections and the other for crossroads and junctions. Practical and efficient handover procedures, based on the proposed schemes, are also presented. Specifically, an on-board unit (OBU) informs the old road-side unit (RSU) about its departure from the coverage area such that the old RSU can forward the buffered packets to candidate RSUs for proactive caching. In handover scenarios around crossroads and junctions, the IEEE 802.11f Move-notify message is used by the new RSU to request the rest of candidate RSUs to purge the cached packets in order to prevent the waste of radio resource. Simulation results show that the proposed schemes outperform conventional schemes.